If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 12x + -5 = 22 Reorder the terms: 3 + -5 + 12x = 22 Combine like terms: 3 + -5 = -2 -2 + 12x = 22 Solving -2 + 12x = 22 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 12x = 22 + 2 Combine like terms: -2 + 2 = 0 0 + 12x = 22 + 2 12x = 22 + 2 Combine like terms: 22 + 2 = 24 12x = 24 Divide each side by '12'. x = 2 Simplifying x = 2
| 25(4x+2)=150 | | 8x+3y-5x+7-10y+2= | | 4x-12x-12x+36=4x^2+36 | | (7j-h)(7j-h)(7j-h)= | | x^2+105=5 | | ln(2)=.69 | | 3n+5n=8 | | 1-x-6x=-6 | | X+6-3=-3 | | 13(9x-6)=6x-4 | | w+1.2=16.2 | | 12.12=3v | | (4x-5y+3z)+(-4x+5y+3z)= | | 2(3R-2)=4(R+4) | | -139-2x=57-9x | | 15+4x=7x+48 | | 12-(x-12)=4 | | 3(1-3x)=-8g+14 | | -2(5+5x)=-120 | | 20=3x-x+6 | | -3(7x+4)=-12 | | -7=5x+7x-7 | | 12-3(2x+1)=4w-21 | | 35(5)+.08x=25(5)+.25x | | 33xy/3x | | -2x+2-6x=34 | | 3(45)+6x=303 | | 2x+2-6x=34 | | 5n-10=8n-14 | | 12x-3=20x-9 | | 4x-3+2x-x=10 | | 7/9×1/5 |